IDEOLOGY IN THE LANGUAGE OF THE ISLAMIC REPUBLIC OF IRAN BROADCASTING REGARDING IRANIAN NUCLEAR POLICY: A CRITICAL DISCOURSE ANALYSIS - Kulmamatov, Komil (2014)
This study examines how nuclear program is depicted in the official media Iran, IRIB (Islamic Republic of Iran Broadcasting). This also shows the ideology in pursuing political interest are also explained in this study. Employing Critical Discourse Analysis framework from Theo van Leeuwen, three levels of analyses, i.e. exclusion, inclusion, and social analysis are used to examine 10 news texts published between 2011 and 2014 containing statements made by President Mahmoud Ahmadinejad and the cancellation of Iran's negotiation. Analyses show that IRIB has strong tendencies to defend Iran and its nuclear policies. Ideology in their news is conservativism, to conserve highest ideal of the 1979 Islamic Revolution. Keyword: Representation, Discourse, Iranian Nuclear, IRIB